2015
DOI: 10.1530/erc-14-0546
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary tumors contain a side population with tumor stem cell-associated characteristics

Abstract: Pituitary adenomas cause significant endocrine and mass-related morbidity. Little is known about the mechanisms that underlie pituitary tumor pathogenesis. In the present study, we searched for a side population (SP) in pituitary tumors representing cells with high efflux capacity and potentially enriched for tumor stem cells (TSCs). Human pituitary adenomas contain a SP irrespective of hormonal phenotype. This adenoma SP, as well as the purified SP (pSP) that is depleted from endothelial and immune cells, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 61 publications
7
91
2
Order By: Relevance
“…The same mechanism has also been suggested to give rise to tumours characterized by uncontrolled cell division. Notably, previous studies have demonstrated the presence of stem cells through SOX2 and SOX9 expression in pituitary adenoma and ACP [5,6,17,23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same mechanism has also been suggested to give rise to tumours characterized by uncontrolled cell division. Notably, previous studies have demonstrated the presence of stem cells through SOX2 and SOX9 expression in pituitary adenoma and ACP [5,6,17,23]. …”
Section: Discussionmentioning
confidence: 99%
“…They have been demonstrated to form pituitary spheres and to secrete hormones in culture [5,6]. Pituitary adenomas are benign tumours, but their hormone production and associated growth disorders are related to increased morbidity [7].…”
Section: Introductionmentioning
confidence: 99%
“…This indirect paracrine function of stem cells is of relevance to human pituitary tumour formation, as this mouse model recapitulates the most common paediatric pituitary tumour, adamantinomatous craniopharyngioma, also harbouring mutations in CTNNB1 activating the WNT signalling pathway. There is evidence of cells isolated from pituitary adenomas with similarities in their in vitro capacity and gene expression to pituitary stem cells [46]. These are also defined by a side population efflux profile upon flow cytometry following Hoechst dye labelling, which can be enriched for stem cells in many tissue types, including the pituitary [47].…”
Section: Signalling Pathways In the Control Of Proliferative Functionmentioning
confidence: 99%
“…Pituitary adenoma stem-like cells were first isolated from a case of human nonfunctional adenoma and another case of human somatotrophic adenoma, respectively, by Xu [20]. Their existence was established in several recent studies [2123]. Stem cell markers are widely used for the identification of TSLCs.…”
Section: Introductionmentioning
confidence: 99%